2‐(8‐Iodonaphthalen‐1‐yl)‐Substituted Nitronyl Nitroxide: Suppressed Reactivity of Iodine Atom and Unusual Temperature Dynamics of the EPR Spectrum. Issue 17 (24th March 2021) - Tretyakov, Evgeny V.; Lomanovich, Konstantin A.; Bagryanskaya, Elena G.; Romanenko, Galina V.; Bogomyakov, Artem S.; Zueva, Ekaterina M.; Petrova, Maria M.; Dmitriev, Alexey A.; Gritsan, Nina P.
Abstract: While developing methods for obtaining high‐spin graphene nanostructures, we carried out a model cross‐coupling reaction between 1, 8‐diiodonaphthalene and an organogold derivative of a nitronyl nitroxide. It was found that only one iodine atom reacted, leading to the corresponding 8‐iodonaphthalen‐1‐yl‐substituted nitronyl nitroxide. The latter was successfully isolated as two polymorphic modifications, whose X‐ray structural analysis revealed a strong distortion of the paramagnet's geometry in comparison with a noniodinated analog. Moreover, the spatial proximity of the heavy iodine atom and the paramagnetic moiety resulted in unprecedented temperature dynamics of the EPR spectrum. To clarify these dynamics, quantum chemical calculations were performed using the exact two‐component relativistic X2C method with the self‐consistent account of spin‐orbit coupling in conjunction with the B3LYP functional and relativistic STO‐type basis set. These computations predicted a reasonable a iso ( 127 I) value that can affect the EPR spectrum. Substitution of the second iodine atom would lead to the formation of a diradical with a 1, 8‐naphthalenediyl bridge, whose structure and magnetic properties were analyzed at the DFT level. Two stable conformations of the diradical with strongly distorted geometry were identified. In both conformations, calculations predict a ferromagnetic exchange between the paramagnetic centers with J =8 and 14 cm −1 ( H=−2 J⋅S1 S2 ). Abstract : The cross‐coupling of 1, 8‐diiodonaphthalene with an organogold nitronyl nitroxide stops at the monoradical with iodine atom at the peri‐position toward the paramagnetic moiety. This arrangement causes a strong distortion of the nitroxide geometry and unprecedented temperature dynamics of the EPR spectrum. The latter can be explained by assuming different characteristic temperatures for averaging the anisotropy of the HFC tensors for N and I atoms.